A Universal Soaking Strategy to Convert Composite Hydrogels into Extremely Tough and Rapidly Recoverable Double‐Network Hydrogels. Issue 33 (14th June 2016) - Yang, Yanyu; Wang, Xing; Yang, Fei; Shen, Hong; Wu, Decheng
Abstract : Soak n' Boost: A universal strategy to manufacture hybrid double‐network hydrogels with eminent mechanical properties is developed by postformation of the chitosan microcrystalline and chain‐entanglement physical networks via simple treatment of the chitosan composite hydrogels using alkaline and saline solutions. The strategy may open an avenue to fabricate multifarious double‐network hydrogels for promising applications in antifouling materials, drug delivery, and tissue engineering.